2006
DOI: 10.1111/j.1440-1843.2006.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated altitude during sleep on moderate‐severity OSA

Abstract: Moderate severity OSA at sea level (60 m) was completely replaced by severe CSA at a simulated altitude of 2750 m. The authors believe that the OSA resolved because of an increased respiratory drive [corrected] and an increase in upper airway tone, whereas CSA developed because of hypocapnia in non-rapid eye movement sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
2
28
2
Order By: Relevance
“…Our study demonstrated similar findings, but our participants who experienced altitude without PAP had less development of central apnea events than in previous studies, perhaps in part due to the administration of supplemental oxygen (4,7). Participants in the Burgess study ORIGINAL RESEARCH were exposed to simulated altitude over a 4-hour period before the 8-hour sleep study, to allow for greater hypoxic stimulus.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our study demonstrated similar findings, but our participants who experienced altitude without PAP had less development of central apnea events than in previous studies, perhaps in part due to the administration of supplemental oxygen (4,7). Participants in the Burgess study ORIGINAL RESEARCH were exposed to simulated altitude over a 4-hour period before the 8-hour sleep study, to allow for greater hypoxic stimulus.…”
Section: Discussionsupporting
confidence: 66%
“…The primary outcome was the AHI. Power analysis and sample size were calculated using data from a previous study (4). Nine participants would sufficiently power the study (b = 0.80) to detect minimally important differences in primary outcome (a = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AHI due to obstructive apnea at 60 m, 610 m, and 2750 m was 25.5, 17.3, and 0.5, respectively; the AHI from central apnea was 0.38, 8.1, and 78.8, respectively at the same altitudes. 12 In this report we describe a presumptive diagnosis of HAPE and its successful treatment with nasal CPAP. Additionally, we present longitudinal data to suggest that increasing altitude was associated with 1) a progressive increase in auto-adjusted CPAP, and 2) a progressive marked increase in the number of apneic and hypopneic episodes occurring during nasal CPAP use.…”
Section: Discussionmentioning
confidence: 89%
“…[1][2][3][4] Overall apnea-hypopnea index (AHI) is higher for individuals with obstructive sleep apnea (OSA), and obstructive events convert to predominately central events at altitude. 5 This degree of respiratory disturbance is corrected in part by moving affected individuals from altitude to sea level. 6 Clinically, our sleep laboratories at altitude have noted increased diffi culty in treating OSA patients with positive airway pressure (PAP).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%